BUSINESS PROCES MANGEMNET SYSTEMS AS A NEW PARADIGM OF IT DEVELOPMENT - Igor G. Fiodorov (Статистика и экономика)
It would be wrong to reduce the paradigm shift in IT development to a change in technology, the emergence of new software or hardware. The development of enterprise information systems based on the BPM is a radical change in our views on methods for business process modeling and for organisation management.